Tele-support in breastfeeding: position statement of the Italian society of Neonatology - Riccardo Davanzo; Maria Enrica Bettinelli; Mariella Baldassarre; Isabella Mondello; Antonella Soldi; Silvia Perugi; Maria Lorella Giannì; Lorenzo Colombo; Guglielmo Salvatori; Laura Travan; Giuseppe Giordano; Breastfeeding Section of the Italian Society of Neonatology (BMC, 2024)
Abstract Tele-support in breastfeeding can be defined as any support provided by a service that connects health workers and/or lactation consultants with breastfeeding parents through video visits, although a telephone contact with the breastfeeding mother remains the first method of remote breastfeeding support. The tele-support in breastfeeding has increased significantly during the SARS-CoV2 pandemic worldwide and, given its effectiveness, may be maintained also after the pandemic. The Italian Society of Neonatology on the basis of: 1) two focus group studies on the tele-support in breastfeeding conducted in Italy with 11 Neonatal Intensive Care Unit nurses and 10 neonatologists, respectively, 2) a national survey on tele-support in breastfeeding addressing the Italian Neonatal Intensive Care Units, and 3) a review of the available experiences and literature, has provided a Position Statement, limitedly to the individual tele-support in breastfeeding. The Italian Society of Neonatology states that: 1) the tele-support in breastfeeding can be used when a consultation in person is not shortly available and may allow to select those situations that require an in-person visit; 2) the organization of a tele-support in breastfeeding session requires the use of a competent, dedicated healthcare staff (specifically trained and/or with adequate experience) and an appropriate methodology while preparing, running and concluding the support session. According to Italian Society of Neonatology the tele-support in breastfeeding may be an effective intervention to promote breastfeeding as a complementary method to the in-person assistance and should be possibly provided in an integrated manner by the Community Health Services and the Maternity Hospital.